(untitled) (European Journal of Pure and Applied Mathematics, 2020)
In microgrid operation, one of the most vital tasks of the system control is to wisely decide between selling excess power to the local grid or charge the Battery Energy Storage System (BESS). Our study uses Mixed-Integer Linear Programming to investigate the impact of storage system on the operational cost of a microgrid. The results suggested that the presence of BESS would relieve the pressure on the utility grid but not the cost of electricity due to the expensiveÂ nature of the storage plant. In view of this, it will be more beneficial to sell excess renewable generated power to the utility grid than to invest in a storage system for larger microgrids.